Reducing complexity in securing heterogeneous networks. (October 2015) - Harrison, Reuven
Abstract : Organisations seeking true agility need a fast, efficient way to visualise and manage the security of all areas of their hybrid environments. A silo approach, will just not work. The changing nature of organisations' IT systems and networks demands that we rethink traditional approaches to security. Virtualisation and cloud computing have been major catalysts for change. And organisations seeking true agility need a fast, efficient way to visualise and manage the security of all areas of these hybrid environments. In this far more complex kind of environment, a silo approach, will just not work, argues Reuven Harrison of Tufin.